2018
DOI: 10.1158/2326-6066.cir-17-0475
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Activity of PD-1/PD-L1 Inhibitors in Metastatic Non–Clear Cell Renal Cell Carcinoma

Abstract: Programmed death 1 (PD-1) and PD ligand 1 (PD-L1) inhibitors have shown activity in metastatic clear cell renal cell carcinoma (ccRCC). Data on the activity of these agents in patients with non-clear cell RCC (nccRCC) or patients with sarcomatoid/rhabdoid differentiation are limited. In this multicenter analysis, we explored the efficacy of PD-1/PD-L1 inhibitors in patients with nccRCC or sarcomatoid/rhabdoid differentiation. Baseline and follow-up demographic, clinical, treatment, and radiographic data were c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(101 citation statements)
references
References 29 publications
2
94
1
1
Order By: Relevance
“…Even though only six patients were treatment naive, they had a numerically higher ORR ( n = 3/6, 50%) in comparison with the reported ORR with sunitinib in nccRCC. We also report that the ORR and DCR were 18.6% and 53.4%, respectively, in a meta‐analysis of 124 patients from published series of metastatic nccRCC and ccRCC >20% rhabdoid patients treated with PD‐1/PD‐L1 checkpoint inhibitors . The observed best ORR with nivolumab in patients with metastatic nccRCC is consistent with the reported activity in ccRCC .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Even though only six patients were treatment naive, they had a numerically higher ORR ( n = 3/6, 50%) in comparison with the reported ORR with sunitinib in nccRCC. We also report that the ORR and DCR were 18.6% and 53.4%, respectively, in a meta‐analysis of 124 patients from published series of metastatic nccRCC and ccRCC >20% rhabdoid patients treated with PD‐1/PD‐L1 checkpoint inhibitors . The observed best ORR with nivolumab in patients with metastatic nccRCC is consistent with the reported activity in ccRCC .…”
Section: Discussionsupporting
confidence: 85%
“…In our review of the literature, we identified two retrospective studies in patients with metastatic nccRCC who received PD‐1/PD‐L1 checkpoints blockade that reported the best ORR by tumor histology . We identified 124 patients with nccRCC and ccRCC histology with >20% rhabdoid and 112 patients with evaluable response rates to PD‐1/PD‐L1 checkpoint inhibitors to be included in our meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunotherapies such as programmed death‐1 (PD‐1)/programmed death ligand 1 (PD‐L1) inhibitors or tumor vaccine are becoming favorable novel treating approach for KIRP. The PD‐1/PD‐L1 blockade demonstrated modest antitumor activity in KIRP patients, with the response rate being approximately 30%, which are much higher than that of clear cell type. Besides, other studies found that a tumor vaccine called TroVax® which expressed the 5 T4 tumor‐associated antigen exhibited robust efficacy and safety in renal cell cancer patients including KIRP patients in clinical trials .…”
Section: Introductionmentioning
confidence: 98%
“…In this issue of The Oncologist , Dr. Chahoud and colleagues report their experience using nivolumab alone or in combination with ipilimumab or VEGF‐targeted therapies to treat patients with metastatic nccRCC at MD Anderson Cancer Center (MDACC) . Because their study is the third retrospective analysis of nivolumab in metastatic nccRCC, the authors also performed a meta‐analysis of these studies . In the MDACC experience, the objective response rate (ORR) was 20.6%, with a complete response (CR) rate of 8% in a heavily pretreated cohort in which 50% of patients received nivolumab as third‐line or later treatment.…”
Section: Outcomes Of Clinical Trials or Retrospective Studies For Patmentioning
confidence: 99%